Neurobehavioral and Gene Expression Effects of Early Embryonic Methylmercury Exposure in Yellow Perch (Perca flavescens) and Zebrafish (Danio rerio) Larvae - (:unkn) unknown (My University, 2015)
Methylmercury (MeHg) is a pervasive and persistent neurotoxic environmental pollutant known to affect the behavior of fish, birds and mammals. The present study addresses the neurobehavioral and gene expression effects of MeHg in yellow perch (Perca flavescens) and zebrafish (Danio rerio) embryos. The rationale for this study originated from an interest to understand the behavioral and molecular phenotypes of environmental MeHg exposure in the yellow perch, an ecologically and economically relevant species of the North American Great Lakes region. Both MeHg and the yellow perch coexist in a common ecosystem: the North American Great Lakes. However, the effects of this organism-contaminant interaction are poorly understood. The zebrafish was utilized here as a surrogate model for yellow perch, due to its ease of rearing, whole sequenced genome and its status as an NIH endorsed model organism. The objectives of this study were to understand the effects of MeHg on behaviors that are critical for survival both in yellow perch and zebrafish. Among the behavioral paradigms tested, this study addressed fundamental behaviors for the survival of young larval fish, namely swimming and prey capture. Furthermore, this study screened for gene expression alterations in the same cohorts of fish for which behavioral analysis was performed; this was done to gain insight into the gene pathways involved in MeHg-induced neurotoxicity, as well as to expand the knowledge about biomarkers of MeHg exposure in the yellow perch. Here, we have uncovered important differences and similarities between the effects of MeHg exposure in yellow perch and zebrafish larvae, both in terms of behavioral and molecular responses to MeHg. The findings of this study suggest that environmentally relevant MeHg exposure can adversely affect the behavior of yellow perch larvae and impair fundamental survival skills. Furthermore, this study determined that although it would be challenging to relate behavioral endpoints between yellow perch and zebrafish, molecular responses between these two species could be more conserved.
Keywords: Behavior; Gene Expression; Methylmercury; Yellow Perch; Zebrafish